Research progress on composite nerve guidance conduits with immune-regulatory functions - Zhang, Shuxuan; Sun, Xinyue; Yang, Xuewa; Fan, Yulan; Liang, Yuxin; Li, Jiaying; Ling, Jue (Frontiers in Immunology, 2025)
Peripheral nerve injury (PNI) has emerged as a critical clinical challenge due to its high disability rate and socioeconomic burden. Traditional autologous nerve grafting, limited by donor shortages and risks of secondary surgeries, has driven tissue-engineered nerve conduits to become a research hotspot. This review systematically summarizes recent advances in immunomodulatory nerve conduits, focusing on the biological properties, degradation mechanisms, and pivotal roles of natural materials (e.g., collagen, chitosan, silk fibroin) and synthetic materials (e.g., poly (lactic-co-glycolic acid) (PLGA), polylactic acid (PLA), and polycaprolactone (PCL) in regulating macrophage polarization. The potential of composite materials to synergistically optimize mechanical performance and bioactivity of nerve conduits is also discussed. Furthermore, this review envisions future trends in nerve conduits, including the integration of 4D printing, smart-responsive systems, and personalized designs to overcome current therapeutic limitations. By integrating multidisciplinary perspectives from materials science, immunology, and regenerative medicine, this review aims to provide innovative theoretical frameworks and technical pathways for efficiently repairing PNI, advancing clinical translation.